Jordi Savall conducts Bach's Concertos and Orchestral Suites With Le Concert des Nations - Bach, Johann Sebastian 1685-1750; Bach, Johann Sebastian 1685-1750; Bach, Johann Sebastian 1685-1750; Bach, Johann Sebastian 1685-1750; Handel, George Frideric 1685-1759; Marais, Marin 1656-1728 (Karl More Productions, Cima, Mezzo, 2013)
Every year since 2006 at Narbonne's Fontfroide Abbey, the acclaimed International Festival "Music and History for Intercultural Dialogue" takes place. As part of the 2013 Festival, artistic director and renowned viola da gambist Jordi Savall led the Concert des Nations (flutist Marc Hantaï, harpsichordist Pierre Hantaï, violinists Manfredo Kraemer and Riccardo Minassi, oboist Paolo Grazzi, and bassoonist Claude Wassmer) in a beautiful selection of concertos and orchestral suites by the inimitable German baroque composer Johann Sebastian Bach alongside the Bourrée from G.F. Handel's Water Music Suite in F Major and the "Marche pour les Matelots" from Marin Marais's opera Alcyone
Keywords: concert; Internet videos